Start with the heart : igniting hope in schools through social and emotional learning - Trujillo, Michelle L., 1967- (Thousand Oaks : Corwin, 2019)
Start with the heart to build a school climate in which achievement will flourish. You can build an empathetic school culture that promotes genuine acceptance of one another, an appreciation for diversity, and an intrinsic desire to contribute and grow academically-a school environment that is inviting, positive, and engaging! In this easy-to-read, inspiring book, educational consultant and former high school principal Michelle Trujillo shows how positive school culture is anchored in social and emotional learning as a way of being. Through explanation, personal anecdotes, and the demonstration of problem-solving through intentional connection, she guides educators to explore their own SEL aptitudes. In doing so, she inspires a schoolwide investment in a philosophy of connection-with students and each other-that ignites a climate in which every individual is seen, heard, and valued, and academic achievement has an opportunity to thrive for all. Drawing in readers through story and reflection, the book defines the challenges educators face and offers ample tools, strategies, and solutions for integrating 5 SEL competencies into schools. It includes Concrete examples of relationship-building in action in schools by modeling, integrating and explicitly teaching social and emotional learning (SEL) to students Practical, evidence-based strategies for explicit teaching of each SEL competency to students Opportunities for reflection, brainstorming, and classroom planning Stories that bring the student experience of empathetic school culture to life References to programs and practices that meet Tier 1 and 2 evidence-based curriculum requirements. Jumpstart conscientious connections in your school community and create a foundation for trust that allows students and educators to feel appreciated, effective, and productive.'This is a powerful and moving resource to inspire every educator who wants to make a difference!' -- Eric Jensen, Author, Brain-Based Learning and Teaching With the Brain in Mind
Includes bibliographical references and index.
Description based on XML content.
Keywords: Affective education; Social learning; Self-consciousness (Awareness); Teachers -- Conduct of life; Teacher-student relationships